Gene expression network analysis identified CDK1 and KIF11 as possible key molecules in the development of colorectal cancer from normal tissues - Soo Bin Lee; Young Seon Noh; Ji-Wook Moon; Soohyun Sim; Sung Won Han; Eun Sun Kim; Ji-Yun Lee (Genomics & Informatics)
Abstract Background Colorectal cancer (CRC) is one of the most common malignancies and the second most common cause of cancer-related mortality worldwide. Despite extensive research, the mechanism underlying CRC development remains unclear. This study aimed to understand the development and progression of CRC. Methods Gene network analysis of tumors with their paired normal tissues was performed using the differentially expressed genes dataset for CRC from the Cancer Genome Atlas. Further investigation of the regulatory relationship between hub genes and tumor development was conducted by protein–protein interaction network, Gene Ontology enrichment, and Kyoto Encyclopedia of Genes and Genomes pathway analyses using the selected hub genes. Results The network was more centered, and a common hub as well as a hub of hub genes were more connected to each other in the tumor than in the normal tissue, indicating changes in the network from normal to tumor. Eight downregulated and two upregulated hub genes (CDK1 and KIF11) in the tumor were identified. Further, the regulatory pathway was altered, especially in cell cycle and cell division. All R implementation codes are available on the journal website as supplementary materials. Conclusions Our findings may help understand the biological processes underlying tumor development and progression and suggest CDK1 and KIF11 as possible key molecules in the development of CRC.